Clinical and genomic features of SPOP‐mutant prostate cancer. Issue 2 (15th November 2021) - Nakazawa, Mari; Fang, Mike; H. Marshall, Catherine; Lotan, Tamara L.; Isaacsson Velho, Pedro; Antonarakis, Emmanuel S.
Abstract: Background: Inactivating missense mutations in the SPOP gene, encoding speckle‐type poxvirus and zinc‐finger protein, are one of the most common genetic alterations in prostate cancer. Methods: We retrospectively identified 72 consecutive prostate cancer patients with somatic SPOP mutations, through next‐generation sequencing analysis, who were treated at the Johns Hopkins Hospital. We evaluated clinical and genomic characteristics of this SPOP ‐mutant subset. Results: SPOP alterations were clustered in the MATH domain, with hotspot mutations involving the F133 and F102 residues. The most frequent concurrent genetic alterations were in APC (16/72 [22%]), PTEN (13/72 [18%]), and TP53 (11/72 [15%]). SPOP ‐mutant cancers appeared to be mutually exclusive with tumors harboring the TMPRSS2‐ERG fusion, and were significantly enriched for Wnt pathway ( APC, CTNNB1 ) mutations and de‐enriched for TP53/PTEN/RB1 alterations. Patients with mt SPOP had durable responses to androgen deprivation therapy (ADT) with a median time‐to‐castration‐resistance of 42.0 (95% confidence interval [CI], 25.7–60.8) months. However, time‐to‐castration‐resistance was significantly shorter in SPOP ‐mutant patients with concurrent TP53 mutations (hazard ratio [HR] 4.53; p  = 0.002), HRD pathway ( ATM, BRCA1/2, and CHEK2 ) mutations (HR 3.19; p  = 0.003), and PI3K pathway ( PTEN, PIK3CA, and AKT1 ) alterations (HR 2.69; p  = 0.004). In the castration‐resistant prostate cancer setting, median progression‐free survival was 8.9 (95% CI, 6.7–NR) months on abiraterone and 7.3 (95% CI, 3.2–NR) months on enzalutamide. There were no responses to PARP inhibitor treatment. Conclusions: SPOP ‐mutant prostate cancers represent a unique subset with absent ERG fusions and frequent Wnt pathway alterations, with potentially greater dependency on androgen signaling and enhanced responsiveness to ADT. Outcomes are best for SPOP ‐altered patients without other concurrent mutations.